2D characterization of near‐surface VP/VS: surface‐wave dispersion inversion versus refraction tomography. Issue 4 (1st April 2015) - Pasquet, Sylvain; Bodet, Ludovic; Longuevergne, Laurent; Dhemaied, Amine; Camerlynck, Christian; Rejiba, Fayçal; Guérin, Roger
ABSTRACT: The joint study of pressure (P‐) and shear (S‐) wave velocities ( V P and V S ), as well as their ratio ( V P / V S ), has been used for many years at large scales but remains marginal in near‐surface applications. For these applications, V P and V S are generally retrieved with seismic refraction tomography combining P and SH (shear‐horizontal) waves, thus requiring two separate acquisitions. Surface‐wave prospecting methods are proposed here as an alternative to SH‐wave tomography in order to retrieve pseudo‐2D V S sections from typical P‐wave shot gathers and assess the applicability of combined P‐wave refraction tomography and surface‐wave dispersion analysis to estimate V P / V S ratio. We carried out a simultaneous P‐ and surface‐wave survey on a well‐characterized granite‐micaschists contact at Plœmeur hydrological observatory (France), supplemented with an SH‐wave acquisition along the same line in order to compare V S results obtained from SH‐wave refraction tomography and surface‐wave profiling. Travel‐time tomography was performed with P‐ and SH‐ wave first arrivals observed along the line to retrieve V P t o m o and V S t o m o models. Windowing and stacking techniques were then used to extract evenly spaced dispersion data from P‐wave shot gathers along the line. Successive 1D Monte Carlo inversions of these dispersion data were performed using fixed V p values extracted from the V P t o m o model and no lateral constraints between two adjacent 1D inversions. The resulting 1D V S s w models were then assembled to create a pseudo‐2D V S s w section, which appears to be correctly matching the general features observed on the V S t o m o section. If the V S s w pseudo‐section is characterized by strong velocity uncertainties in the deepest layers, it provides a more detailed description of the lateral variations in the shallow layers. Theoretical dispersion curves were also computed along the line with both V S t o m o and V S s w models. While the dispersion curves computed from V S s w models provide results consistent with the coherent maxima observed on dispersion images, dispersion curves computed from V S s w models are generally not fitting the observed propagation modes at low frequency. Surface‐wave analysis could therefore improve V s models both in terms of reliability and ability to describe lateral variations. Finally, we were able to compute VP / VS sections from both V S s w and V S t o m o models. The two sections present similar features, but the section obtained from V S s w shows a higher lateral resolution and is consistent with the features observed on electrical resistivity tomography, thus validating our approach for retrieving VP / VS ratio from combined P‐wave tomography and surface‐wave profiling.